Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fenvs.2022.945091
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Dynamic Relationship Between Energy Efficiency, Trade, Economic Growth, and CO2 Emissions: Evidence From Novel Fourier ARDL Approach

Abstract: Climate change, energy security, and volatile energy prices have been emerging as eminent threats worldwide. To overcome these concerns, energy efficiency could play a positive role. Hence, this study probes whether energy efficiency curbs CO2 emissions in the US, while controlling for trade, economic growth, and population. We use the Fourier-ADF and Fourier-LM tests to discern the unit-roots. Moreover, to render reliable findings, we rely on the novel Fourier ARDL model. The study divulges that energy effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 68 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…However, Hashmi et al [ 37 ] study in USA indicated that climate policy uncertainty worsens carbon emissions in both short and long-runs in residential, commercial, and electric power sectors. In addition, Liu et al [ 38 ] study indicated that energy efficiency in both the long and short runs helps curb emissions. Makhdum et al [ 39 ] study also indicated that renewable energy helps diminish ecological footprint.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, Hashmi et al [ 37 ] study in USA indicated that climate policy uncertainty worsens carbon emissions in both short and long-runs in residential, commercial, and electric power sectors. In addition, Liu et al [ 38 ] study indicated that energy efficiency in both the long and short runs helps curb emissions. Makhdum et al [ 39 ] study also indicated that renewable energy helps diminish ecological footprint.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There has been an intense debate in the energy and environmental function discourse on the inclusion of urbanization, especially regarding regional and environmental development. However, few works Poumanyvong and Kaneko (2010), , Sheng et al (2017), Lui (2019), Jiang et al (2022), Liu et al (2022), andWen et al (2022) have documented the long relationship between urbanization and energy consumption and environmental quality. analyzed the impact of urbanization on renewable and non-renewable energy consumption in OECD countries using the STIRPAT model and data from 1980 to 2011.…”
Section: Energy Consumption and Urbanization Nexusmentioning
confidence: 99%
“…They analyzed the environment degradation proxied by CO 2 emission on the profile of chosen higher CO 2 emissions economies. According to Liu et al [23], energy consumption has a positive and statistically significant influence on CO 2 emissions for BRIC nations in the longterm equilibrium. Numerous studies looked at the connection between CO 2 emissions and economic growth at the national level.…”
Section: Greenhouse Gases and Economic Growthmentioning
confidence: 99%